Coccoliths and oxygen isotope observations from the sediment surface of the southwest Indian Ocean - Fincham, Mark J (Department of Oceanography, 2017)
The interplay of three important parameters, dissolution, dilution and winnowing seem to be controlling the state in which sediment material is preserved in the study area though most samples examined under the SEM were generally well preserved. The distribution of forty-four coccolithophore species in one hundred deep sea core-tops from the southwest Indian Ocean is described. Three coccolith assemblages have been recognised (Maputo, Agulhas Current and deep water) and are delineated by the relative abundances of four ecologically significant coccolithophore species (Gephyrocapsa oceanica, Emiliania huxleyi, Calcidiscus leptoporus and Umbilicosphaera sibogae). These four species are the most abundant in the study area and the major factors influencing their geographical distribution seem to be temperature, nutrient concentration and dissolution. Coccolith and foraminifera preservations indicate that the carbonate lysocline lies somewhere between 3500 and 4000 meters, resulting in the concentration of dissolution resistant microfossils below this depth. Stable oxygen isotope ratios in a planktonic foraminifera and percent abundances of E. huxleyi reveal that apart from cores taken in the Agulhas Passage, most of the core-top samples are probably less than 85,000 yrs. BP. Lightest isotope ratios of -1.5 to -1.0 per mil PDB (equal to 22.8 to 25.1°C) occur in a narrow band on the sea floor beneath the "A" route of the Agulhas Current. These values are about 0.5 per mil PDB lighter than samples analyzed on either side of this band and can be explained by the Agulhas Current's elevated temperature at the ocean surface of between 2 to 3°C. Thus, an oxygen isotope imprint of the Agulhas Current exists beneath it on the sea floor. The Agulhas Current is probably the major factor influencing sedimentation, sediment distribution patterns and geological features in the study area. At present it is voluminous and fast flowing, possibly eroding sediments 2500 meters below the surface. The oxygen-isotope ratios and nannoplankton counts obtained in this study indicate however, that the majority of samples are most probably recent or at least not older than 85,000 years except for sediments found in the Agulhas Passage. This implies that sediments are accumulating on the ocean floor and that the current does not have a pronounced erosional influence, at least in areas from which cores were retrieved for this study.